Economic Value Added and Traditional Accounting Measures for Shareholder’s Wealth Creation - Panigrahi, Shrikant (Universiti Kebangsaan Malaysia, 2017)
This paper investigated performance measurement tools and shareholder’s wealth relationships in the context of Malaysian public listed construction companies. Conventional measures are still utilized by many Malaysian listed companies even though it has been criticized by many researchers. Both traditional accounting measures and economic measures fail to reflect a company’s true value due to the lack of long-term sustainability of a business. The study used panel data analysis techniques, particularly Error Correction Models (ECM) to test the relationship of error terms and panel Ordinary Least Square (OLS) regression to test the hypothesis. Panel data comprised of 280 observations over the period of 2003-2012 indicates that shareholder value is a function of performance measures. The results conclusively support the claims made by previous studies on the role of earnings per share, economic value added (EVA) and dividend payout ratio; and further support the potential usefulness of the performance metric for internal and external performance. Furthermore, market value added (MVA) is found to have a negative relationship with created shareholder value (CSV) contradicting with the theory that confirmed, the increase in shareholder value when there is an increase in stock market value and efficiency